Social capital and its relationship with Universiti Putra Malaysia undergraduates' Facebook usages - Hamsan, Hanina Halimatusaadiah; Kumar, Matthew Naveen; Shahrimin, Mohamad Ibrani (Universiti Putra Malaysia Press, 2013)
This study envisaged in determining the relationship between the intensity of Facebook usage and social capital among undergraduates at Universiti Putra Malaysia. A number of factors (respondent’s personal and family background, the intensity of Facebook usage and social capital) have been studied with regards to their relationships with each other. Respondents involved 120 male and female undergraduates studying at Universiti Putra Malaysia (UPM), who were selected through a convenience sampling. A self-administered questionnaire was used as a tool for data collection. Majority of the respondents were between 21 and 23 years of age, obtained an average of CGPA of 3.05 and came from educated parents (diploma and above), and moderately high household incomes. Pearson correlation was used to test the correlation between the respondent’s personal and family backgrounds with Facebook intensity. Meanwhile, linear regression was used to analyze the strength of the relationship between Facebook intensity and social capital and revealed that all have significant relationships with the intensity of Facebook usage. The linear regression analysis also affirmed that the intensity of the Facebook use (β = 0.274**) has a positive but miniscule effect on the increment of social capital. Relevant factors attributed to findings are also discussed.